Resilience Efforts for Girls Victims of Sexual Violence - Jamil, Nur Aisyah; Yulianty, Nadya (International Conference on Islamic Studies, 2022)
Resilience is the ability to cope with and adapt to severe events or problems that occur in life. The purposes of this study are 1) to see how the traumatic experiences experienced by children who are victims of sexual violence, 2) the efforts that are expected by children who are victims of violence against perpetrators of sexual violence and the events they have experienced, and 3) the efforts made to eliminate traumatic experiences in children. victims of sexual violence. This research uses qualitative research with a case study approach. Meanwhile, in collecting data using the method of observation and in-depth interviews. The data in this study were sourced from children who were victims of sexual violence who had been reported by their families and were under the handling of P2TP2A Purwakarta Regency. P2TP2A is an Integrated Service Center for the Protection of Women and Children who experience violence, whether physical, psychological or sexual violence in the Purwakarta Regency area. The data used are primary and secondary data. The implications of this research are expected to be able to contribute to all parties, both victims, families of victims, perpetrators of sexual violence, the community or parties related to sexual violence against children. In addition, this research is expected to be input for P2TP2A Purwakarta Regency and also related agencies in handling cases of sexual violence or traumatic recovery experienced by girls who are victims of sexual violence.